Enhancement of electrochemical properties using iron oxide-gold nanocomposite for tuberculosis detection based on rGO-APTES modified screen-printed electrode - Syed Amri, Syazana Ameera; Yusof, Nor Azah; Abdullah, Jaafar; Abd Rahman, Siti Fatimah; Mohd Azmi, Umi Zulaikha (Institute of Electrical and Electronics Engineers, 2021)
A new electrochemical immunosensor based on iron oxide-gold nanocomposite (Fe 3 O 4 -Au NC) as signal enhancement was developed for sensitive detection of M. tuberculosis , the causative agent of tuberculosis (TB). Reduced graphene oxide-(3-aminopropyl)-triethoxysilane (rGO-APTES) modified screen-printed electrode (SPE) was employed as a matrix to immobilize the capture antibodies (Ab). The detection signal was amplified due to the large amounts of Ab captured on the large surface area of modified SPE. The Fe 3 O 4 -Au NC were functionalized as label to conjugate with primary antibodies (Ab 1 ). Due to the homogeneity and narrow size distribution of Fe 3 O 4 -Au NC, several Ab 1 were bound on each nanocomposite. The introduction of Fe 3 O 4 -Au-Ab 1 onto the electrode surface through sandwich immunoreactions enhances the performance of the sensor. The proposed immunosensor offered a sensitive detection of TB in the range of 0– 9.0 μg /mL, with a detection limit of 1.32 ng/mL. A disposable and sensitive SPE-based electrochemical immunoassay would serve as a promising platform to detect various mycobacterium pathogens for future diagnostic studies.